MODELING DAN PENYELESAIAN MASALAH PROGRAM LINEAR DENGAN POM-QM FOR WINDOWS - Bernard; Alimuddin; Sahid; Ilham Minggi (Ininnawa : Jurnal Pengabdian Masyarakat, 2023)
Today the use of software has developed in various fields of human life, including the world of education. These developments also have an impact on learning mathematics in general and linear programming as part of mathematics. The software on the computer that is used to solve problems in linear programming material is POM-QM FOR WINDOWS. POM-QM for Windows is a software that can be used to solve various problems related to linear programming material, ranging from very simple problems to more complex problems that are difficult to solve manually. With this software, it is hoped that it can facilitate the process of learning linear program material carried out by teachers in schools. To be able to solve these linear programming problems both manually and by using the POM-QM for Windows software, then of course these problems must be made/formulated in the form of a mathematical model through the model formulation process or what is commonly known as modeling. Modeling is the process of translating real/everyday problems (linear programming problems) into mathematical language (abstract problems).